A Framework for Innovating the Technological Startup in the Cordillera Region through an E-commerce Mobile Platform (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2024)
The technological startup community is beginning to be recognized in solving various needs in the Cordillera region. However, these technological startups have limited growth because they encounter challenges such as financial concerns, limited market reach, lack of awareness of intellectual property rights, and inadequate digital infrastructure. Thus, the researcher proposed the development of an e-commerce mobile application that addresses the needs of startups. Through the use of data gathering techniques, the researcher was able to determine the design considerations in terms of the architecture framework and features of the e-commerce mobile application that addressed the problems encountered by startups in the Cordillera region. The use of the 4+1 view model illustrated the architecture framework of the e-commerce mobile platform for intended stakeholders by providing a logical view, process view, physical view, development view, and scenario view. The architecture framework was used to determine the features to be integrated into the proposed e-commerce mobile application to address the challenges of the technological startups of the Cordillera region.